Au-delà de l’ethnocentrisme : Pour une théorie de la rencontre dans les récits de voyage au xviie siècle - Vanezia Pârlea (Viatica)
The discovery of the Other is an essential issue for any traveller. Through explaining a theory of encounters in 17th-century travel narratives in the Orient, this article highlights the possibilities of encounters. Using significant examples to illustrate the evolution of relationships with the Other, which involves the construction of images and representations as well as a dialogical type of anthropology, the author shows that the question of otherness became increasingly important in the geographical literature of the 17th century.